The Influence of Influencer Marketing and Content Marketing on Rucas. Co Purchasing Decisions: The Mediating Role of Customer Engagement and Moderating Role of Fomo (A Study of Generation Z) - Victor Anugrah Sirait; Yenny Purwati (Green Publisher Indonesia, 2026)
This study aims to analyze the influence of influencer marketing and content marketing on purchase decisions for Rucas.co, with customer engagement as a mediating variable and fear of missing out (FOMO) as a moderating variable. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with a sample of 300 Generation Z respondents in Indonesia. The findings reveal that influencer marketing has a positive and significant effect on purchase decisions, whereas content marketing has a positive but insignificant effect. Furthermore, customer engagement is proven to mediate the relationship between influencer marketing, content marketing, and purchase decisions. In addition, FOMO moderates the relationship between influencer marketing and purchase decisions but does not moderate the relationship between content marketing and purchase decisions. These results suggest that companies, particularly fashion brands such as Rucas.co, should prioritize credible influencer marketing strategies and relevant content to strengthen customer engagement and ultimately drive purchase decisions.